Pengendalian Tegangan Keluaran DC-DC Boost Converter Tipe Voltage Doubler Menggunakan Mikrokontroler STM32F1038CT - Candra, Kevin; Pratomo, Leonardus Heru (Jurnal Teknik Elektro, 2020)
Five-level inverter is widely used in many industrial applications, for example as a three-phase electric motor drive, PLTS, etc. This inverter works using two separated DC voltage sources in order to form different voltage level. Five-level inverter using one DC voltage source will be more efficient. A DC-DC boost converter on Voltage Doubler type is used in order to solve the problem. The focus of this research is on controlling the DC-DC boost converter on Voltage Doubler type. The switch control method uses a shifted pulse width modulation of 1800. To get a suitable output voltage, an output voltage control system is applied. A proportional and integral type control is implemented using STM32F1038CT microcontroller.Ã‚Â  The output voltage controlled DC-DC boost converter is validated through computational simulation with Power Simulator software and as the final step will be implemented on hardware in the laboratory. Based on the simulation and implementation, Voltage-Doubler type of DC-DC boost converter is able to produce the required output voltage, which is two times greater than the conventional DC-DC boost converter output voltage.